2022
DOI: 10.3390/molecules27154745
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Activities of Fermented Curcuma That Contains Butyrate Mitigate DSS-Induced Colitis in Mice

Abstract: Inflammatory bowel disease is characterized by a radical imbalance of inflammatory signaling pathways in the gastrointestinal tract, and it is categorized into two diseases, such as Crohn’s disease and ulcerative colitis. In this study, we investigated anti-inflammatory activities using fermented Curcuma that contains butyrate (FB). Nitric oxide production in RAW 264.7 cells and the expression of inducible nitric oxide synthase in the intestinal mucosa appears to be enhanced in active ulcerative colitis. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In contrast, unfermented turmeric lacks this effect. Bayazid et al found that Clostridium butyricum -fermented turmeric can reduce LPS-induced NO production in RAW264.7, revealing its anti-inflammatory effect [ 31 ]. Lim et al demonstrated that turmeric fermented by R. oligosporus exhibited a 1.44-fold inhibitory effect on LPS-stimulated NO production by RAW264.7 cells after 3 d of fermentation (compared to unfermented turmeric) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, unfermented turmeric lacks this effect. Bayazid et al found that Clostridium butyricum -fermented turmeric can reduce LPS-induced NO production in RAW264.7, revealing its anti-inflammatory effect [ 31 ]. Lim et al demonstrated that turmeric fermented by R. oligosporus exhibited a 1.44-fold inhibitory effect on LPS-stimulated NO production by RAW264.7 cells after 3 d of fermentation (compared to unfermented turmeric) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric kombucha and turmeric kombucha-medicated serum substantially inhibited the LPS-induced increase in inflammatory factors, exhibiting anti-inflammatory activity. Compared to the TW, the turmeric fermentation liquid displayed a stronger protective effect and a more pronounced regulatory impact on the immune system [ 31 ]. Turmeric-based kombucha infusions have the potential to enhance the functional and nutritional values of kombucha.…”
Section: Discussionmentioning
confidence: 99%
“…The gut also produces short-chain fatty acids (SCFAs), which are immensely studied as being bioactive in neurology [33,34]. Disruptions in the integrity of the intestinal barrier can lead to the translocation of gut-derived toxins and inflammatory molecules into the bloodstream, causing systemic inflammation and potentially worsening the immune system, aggravating neuroinflammation and neuronal damage [31,34,35]. The dysbiosis in the gut triggers inflammatory cytokines and mediators, such as tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-γ), interleukins (ILs), lipopolysaccharides (LPS), making a leaky gut.…”
Section: Anthocyanins On Gut−brain Axismentioning
confidence: 99%
“…The brain is particularly vulnerable to oxidative damage due to its high oxygen consumption, abundant lipid content, and relatively low levels of antioxidant defenses. In AD, the balance between reactive oxygen species (ROS) production and the cellular antioxidant capacity is disrupted, leading to increased oxidative stress and subsequent neurological damage [34,35,60,61]. Excessive ROS may cause the abnormal metabolism of amyloid-beta (Aβ) peptide and lead to AD [62,63].…”
Section: Anthocyanins In Oxidative Stressmentioning
confidence: 99%
“…Previous studies have shown that LPS administration significantly increases the expression levels of inflammatory cytokines and mediators in the hippocampus. The expression of TNF-α and IL-1β mRNA is dynamically regulated by immune cells in the hippocampal inflammatory response [ 72 , 73 ]. However, quercetin has shown the ability to mitigate the abnormalities such as anxious behavior and neuroinflammation by consistently lowering LPS-induced IL-6 and IL-1β levels.…”
Section: Metabolism Of Quercetinmentioning
confidence: 99%